Automatic Headlight Dimmer Using Arduino and LDR Sensor (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective of this paper is to design the prototype model of the Automatic headlight dimmer. While travelling during night times the head light of the upcoming vehicle hits the eyes of the driver from the opposite end. Sometimes this bright light from the opposite vehicle causes glare to the drivers and it leads to accident. The sudden glare which the driver experienced is called Troxler Effect. Many reports say that the accidents in roadways during night times are mainly caused by this Troxler Effect. In order to provide safety to the drivers and also for a comfortable travel this model is proposed. It can be achieved by using an LDR sensor. The LDR sensor which acts as a variable resistant that converts the high beam of the upcoming vehicle’s headlight to low beam with the help of Arduino UNO and other components. This system will be a useful in the area of automobile and brings a new trend to ensure the safety of the drivers.